Layout techniques for FPGA switch blocks. - Schmit, H. (IEEE Transactions on VLSI systems)
This paper presents abstract layout techniques for a variety of field-programmable gate array switch block architectures. For subset switch blocks of small size, we find the optimal implementations using a simple metric. We also develop a tractable heuristic that returns the optimal results for small switch blocks and good results for large switch blocks. We show how it is possible to transform universal switch blocks into a subset architecture by using the decomposition property of universal switch blocks. This allows universal switch blocks to exploit the same layout methodologies as presented for subset architectures.